Tinjauan Kriminologi dalam Praktik Pemerasan oleh Oknum Anggota Organisasi Masyarakat dengan Dalih Pengamanan Lingkungan - Ryan Rafi Aziz; Muhammad Zaky (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The occurrence of extortion by individuals associated with community organizations (Ormas) under the guise of neighborhood security in the Pamulang area signifies a departure from the optimal function of Ormas as social agents within the community. This approach engenders dread and discomfort while also underscoring the disparity between legal standards and social reality. This study intends to examine extortion activities through a criminological perspective, specifically utilizing Edwin Sutherland’s Differential Association Theory, and to assess the efficacy of current legal frameworks. The study employs a qualitative research methodology, utilizing in-depth interviews and observations to examine the experiences and viewpoints of both perpetrators and victims, thereby elucidating the formation and perpetuation of deviant conduct within Ormas contexts. The research inquiries examine the role of social learning processes in extortion and the efficacy of existing legal frameworks in resolving this issue. The results demonstrate that criminal behavior in Ormas is acquired through profound social contact, heavily influenced by the frequency, duration, priority, and strength of group relationships. Moreover, inadequate legal penalties, minimal public reporting, and a lack of stringent control of Ormas operations intensify the persistence of these practices. This study advocates for the enhancement of law enforcement, the amendment of Ormas regulations to incorporate more rigorous criminal penalties, and the elevation of public legal literacy to motivate persons to report and counter intimidation.